A step for the valorization of spent yeast through production of iron–peptide complexes — a process optimization study - Ferreira, Carlos (2022)
Given the importance of iron in human nutrition and the significance of waste and by-product valorisation in a circular economy environment, we investigated the effects of protein and iron concentration on the production yield of iron–peptide complexes from spent Saccharomyces cerevisiae. For this purpose, different amounts of protein and iron were used in the complexation process. The results have shown that higher concentrations, although permitting a faster and larger scale process, provide a significantly lower complexation yield, which deems the process less feasible. This is corroborated by fluorescence analysis, which shows a lower degree of complexation with higher protein concentration. In addition, varying the concentration of iron does not change the quality of formed complexes, as evidenced by Fourier transform infrared spectroscopy (FT-IR) analysis. The morphology of all samples was also evaluated using scanning electron microscopy (SEM). Therefore, further studies are needed to optimize the process and to evaluate the best conditions for an economically sound valorization process for iron–peptide complexes. Nonetheless, current results in the development of a new process for the valorisation of spent yeast, in the form of iron-peptide complexes, look promising.